Juridical Analysis of Legal Implementation of Those Who Refuse the Covid-19 Vaccine - Grenaldo Ginting (Journal of Social Research, 2023)
The Covid-19 pandemic has brought many changes to the world, including economic setbacks. So, it needs to be handled with handling efforts in the form of vaccination to form herd immunity. However, this effort still has resistance from people who do not want to carry out the Covid-19 vaccination. This research aims to determine the juridical review of the implementation of the law against those who refuse the Covid-19 vaccine. This research uses normative research methods with literature study data collection techniques obtained from laws, books, journals, and various other information relevant to the research. The results showed that those who refused the Covid-19 vaccine were subject to criminal and administrative sanctions according to presidential regulation number 14 of 2021 in the form of imprisonment for six months to one year or a fine of five hundred thousand to one million rupiahs. However, the World Health Organization advises forcing individuals to vaccinate but suggests a persuasive approach. In addition, the implementation of this law is carried out by looking at the context of the event, and the condition of individuals who do not want to be vaccinated, considering that there are people who should not be vaccinated.